Mitochondria and Autophagy Dysfunction in Glucocorticoid-Induced Ocular Hypertension/Glaucoma Mice Model. (1st February 2020) - Zeng, Wen; Wang, Wenhuan; Wu, Shengyu; Zhu, Xiaolu; Zheng, Tian; Chen, Xiaomin; Ren, Jiangbo; Gong, Yan; Ke, Min
ABSTRACT: Purpose : This study is aimed to investigate the effects of periocular steroids induction on intraocular pressure (IOP), retinal ganglion cells (RGCs) and trabecular meshwork (TM) ultrastructure in glucocorticoid-induced ocular hypertension mice model. Materials and Methods : Dexamethasone-21-acetate (Dex-Ace) was administered through periocular conjunctival fornix injection every 3 days in C57BL/6J mice. Intraocular pressure was measured weekly by rebound tonometry. RGCs were examined with immunofluorescent staining of BRN3a at week 1, 4, and 8. TM morphology was visualized with electron microscopy. Autophagy was evaluated with immunoblotting in TM tissues. Results : Dex-Ace rapidly and significantly induced IOP, which peaked at week 4. The absolute increase in IOP in the Dex-Ace-treated mice was 8.1 ± 1.4 mmHg, a 60% induction ( p < .0001) compared with that in the vehicle-treated mice. The IOP sustained a higher level in the Dex-Ace group from week 4 to week 8. Dex-Ace treatment decreased the number of RGCs in a time-dependent manner, suggesting that high IOP resulted in optic neuropathy. In addition, Dex-Ace thickened trabecular beams and decreased intertrabecular spaces, with marked accumulation of fibrillar and amorphous granular extracellular material. Moreover, Dex-Ace induced swollen and elongated mitochondria in TM cells. The average mitochondria area was 0.090 ± 0.044 µm 2 in the vehicle-treated mice, and increased to 0.161 ± 0.094 µm 2 ( p < .0001), 0.121 ± 0.029 µm 2 ( p = .0223) and 0.171 ± 0.076 µm 2 ( p < .0001) in the Dex-Ace-treated mice at weeks 1, 4 and 8, respectively. Autophagy was also increased by Dex-Ace treatment, indicating by the upregulation of LC3-I, LC3-II and beclin-1, and downregulation of p62. Conclusion : Dex-Ace administration decreased RGCs and changed TM ultrastructure, mimicking hallmarks of human glucocorticoid-induced glaucoma (GIG). In addition, mitochondria and autophagy dysfunction suggested abnormal energy metabolism in TM cells, which warranted further study to fully elucidate the pathogenesis of GIG.